2017
DOI: 10.1080/23744731.2017.1325706
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of R1234ze(Z) pool boiling heat transfer on horizontal titanium tubes for high-temperature heat pumps

Abstract: R1234ze(Z), which has a global warming potential of less than 1, is a promising alternative refrigerant for hightemperature heat pumps designed for heat recovery in the industrial sector. The use of titanium as the material for heat exchangers exposed to acid exhaust is one solution to prevent oxidation. In this study, the pool boiling heat transfer characteristics outside of horizontal titanium tubes were experimentally investigated for R1234ze(Z). A plain tube and three enhanced titanium tubes were tested at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Nagata and colleagues (2017) also concluded that a correlation from the literature that showed good agreement with the experimental data of the plain copper tube, did not worked well for the enhanced titanium tubes and a second correlation from the literature was proposed for the former tubes. Finally, Nagata et al (2017) observed that at conditions of higher saturation temperatures and lower heat flux, where smaller bubbles were present, the titanium test tubes with smaller fin spaces exhibited higher heat transfer coefficients.…”
Section: Advances In Natural Refrigerants and Low Gwp Refrigerants Flmentioning
confidence: 95%
See 2 more Smart Citations
“…Nagata and colleagues (2017) also concluded that a correlation from the literature that showed good agreement with the experimental data of the plain copper tube, did not worked well for the enhanced titanium tubes and a second correlation from the literature was proposed for the former tubes. Finally, Nagata et al (2017) observed that at conditions of higher saturation temperatures and lower heat flux, where smaller bubbles were present, the titanium test tubes with smaller fin spaces exhibited higher heat transfer coefficients.…”
Section: Advances In Natural Refrigerants and Low Gwp Refrigerants Flmentioning
confidence: 95%
“…The active heat transfer length of the test tube was 400 mm. Nagata et al (2017) concluded that the thermal resistance of the titanium tubes was significantly affected by the lower thermal conductivity of the tube material. However, compared to the plain tube, the tested enhanced tube exhibited a 2.8 to 5.1 times higher heat transfer coefficient, on average, in the test range, and the authors indicated that this could compensate for the disadvantage in the thermal conductivity of titanium.…”
Section: Advances In Natural Refrigerants and Low Gwp Refrigerants Flmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagata et al [70] measured the pool boiling heat transfer for R1234ze(Z) on a plain tube and three enhanced titanium tubes. The depth and the inner width of the reentrant cavities of the enhanced tubes ranged from 0.375 mm to 0.410 mm and from 0.270 mm to 0.310 mm, respectively.…”
Section: Measurements For Low-gwp Refrigerants On Enhanced Surfacesmentioning
confidence: 99%
“…Thanks to zero ODP and low GWP values, the availability of such refrigerants today and in the future is of great importance. The properties of R134a, R1234ze, and R450A are given in Table 1 [13,14].…”
Section: Introductionmentioning
confidence: 99%